2022
DOI: 10.4038/jas.v17i3.9924
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Antioxidant and Active Compounds of <em>Gardenia jasminoides</em> Ellis (GJE) Leaves Extract

Abstract: Purpose:The aim of this study was to isolate and identify the active compound antioxidant fractions from Gardenia jasminoides Ellis leaves. Research Method:The antioxidant activity was determined using DPPH 0.1 mM (1:1), and was analyzed spectrophotometrically. In addition, separation was performed using column chromatography. The most active isolate was identified by UV-Vis, FT-IR, and LC-MS/MS. The quantitative analysis was done in three replicated.Findings: It was discovered that the antioxidant activity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…4.8% chloroxylenol was more effective as a disinfecting agent compared to negative control on the number of bacterial colonies in dental extraction instruments. 19 The USU indicated that the average bacterial count value of the 4.8% chloroxylenol group was lower with 16 AE 6.65 CFU/mL, while the value for the negative control group was 217.50 AE 39.24 (Table 4).…”
Section: Resultsmentioning
confidence: 97%
“…4.8% chloroxylenol was more effective as a disinfecting agent compared to negative control on the number of bacterial colonies in dental extraction instruments. 19 The USU indicated that the average bacterial count value of the 4.8% chloroxylenol group was lower with 16 AE 6.65 CFU/mL, while the value for the negative control group was 217.50 AE 39.24 (Table 4).…”
Section: Resultsmentioning
confidence: 97%